Effectiveness Of The Accreditation Program On Improving The Quality Of Services At Community Health Center X - Rini Herdiani; Rahmat Pannyiwi; Rachmat Ramli (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The community health center accreditation program is a government effort to continuously improve the quality of primary health care services. Accreditation emphasizes quality improvement, patient safety, and service performance. This study aims to determine the effectiveness of the accreditation program in improving service quality at Community Health Center X. This study used a quantitative design with a cross-sectional approach. The research sample consisted of 50 respondents consisting of community health center patients, selected using accidental sampling techniques. Data were collected using a service quality questionnaire based on SERVQUAL dimensions. Data analysis used the Chi- Square test. The results of the study showed that there was a significant relationship between the implementation of the accreditation program and the improvement of service quality at Community Health Center X with a p value <0.05. The conclusion of this study is that the accreditation program is effective in improving the quality of health services at Community Health Center X.